CAR-T cell therapy in advanced thyroid cancer: from basic to clinical - Sun, Zhenhua; Wang, Chaohui; Zhao, Yuyang; Ling, Qingyi (Frontiers in Immunology, 2024)
The majority of patients with thyroid cancer can attain a favorable prognosis with a comprehensive treatment program based on surgical treatment. However, the current treatment options for advanced thyroid cancer are still limited. In recent years, chimeric antigen receptor-modified T-cell (CAR-T) therapy has received widespread attention in the field of oncology treatment. It has achieved remarkable results in the treatment of hematologic tumors. However, due to the constraints of multiple factors, the therapeutic efficacy of CAR-T therapy for solid tumors, including thyroid cancer, has not yet met expectations. This review outlines the fundamental structure and treatment strategies of CAR-T cells, provides an overview of the advancements in both preclinical investigations and clinical trials focusing on targets associated with CAR-T cell therapy in treating thyroid cancer, and discusses the challenges and solutions to CAR-T cell therapy for thyroid cancer.In conclusion, CAR-T cell therapy is a promising therapeutic approach for thyroid cancer, and we hope that our review will provide a timely and updated study of CAR-T cell therapy for thyroid cancer to advance the field.